A Comprehensive Study about the Role of Crosslink Density on the Tribological Behavior of DLC Coated Rubber - Bayrak, Suleyman (Materials (Basel), 2020)
The friction and wear behavior of coated rubber components is strongly dependent on the substrate properties. This work deals with the impact of the crosslink density, i.e., the hardness of the rubber substrate on the tribological performance of uncoated and coated rubber. The hardness of nitrile butadiene rubber (NBR) is varied altering the sulfur content. Both the uncoated and coated rubber samples are characterized in terms of surface and mechanical properties. Tribological tests comprise the examination of the macroscopic contact area and the temperature in the contact zone. It was found that the functional layer enhances the wear resistance significantly. Apparently, the wear and friction behavior of the coated rubber correlates with the hardness and the bulk properties of the substrate material.